Licensure Portability: Assuring Access to Quality Care in Physical Therapy - Mark Lane (International Journal of Telerehabilitation)
The concurrent circumstances of an increasingly mobile workforce, disparities in access to healthcare, and the ability to deliver care through technology (e.g., telehealth) present the need and the opportunity to practice across state borders. Over the past four years, the Federation of State Boards of Physical Therapy (FSBPT) has explored professional licensure models that will allow cross border practice. This paper reviews FSBPT's exploratory process and describes some of the advantages of an interstate compact. It concludes that if agreement among state licensing boards can be achieved, a compact could serve as a viable means to increase patient access to quality physical therapy care.